Quality of Regulatory Pond Development Plan Documents for Barabai Flood Control Against Mandatory LoadsLand Acquisition Planning Document - Nur Amrin, Reza (Marcapada: Jurnal Kebijakan Pertanahan, 2023)
The implementation of land acquisition for the construction of the Barabai flood management pond has been completed successfully and is regarded as a success. One of the factors influencing the success of its execution is land acquisition planning, as stated in the Land Acquisition Planning Document (DPPT). The goal of this research was to assess the quality of the mandatory cargo in the Regulatory Pond Development Plan Document for Flood Control of the Barabai River for the Fiscal Year 2021. The quality of the mandatory cargo for the DPPT is determined using a qualitative technique with descriptive analysis in accordance with Ministerial Regulation Spatial Planning (ATR) /Head of the National Land Agency (BPN) No. 19 of 2021. The document was recognized and examined based on the regulation's mandatory content. Document studies were conducted to acquire data by studying the contents of the DPPT. The study revealed that there are 38 descriptions that must be met in order to create the DPPT. A total of 29 descriptions in the planning document have been thoroughly examined in their analysis, while nine descriptions require further discussion in the document. The presence of more favorable than bad descriptors in the DPPT implies that the stages of land acquisition planning and implementation are in sync. The presence of more favorable than bad descriptors in the DPPT implies that the stages of land acquisition planning and implementation are in sync. Mean¬whi¬le, the nine descriptors must be examined in greater depth in the document. The presence of more favorable than bad descriptors in the DPPT implies that the stages of land acquisition planning and implementation are in sync.